Perpetuating effects of androgen deficiency on insulin resistance - Cameron, J L; Jain, R; Rais, M; White, A E; Beer, T M; Kievit, P; Winters-Stone, K; Messaoudi, I; Varlamov, O (International Journal of Obesity, 2016)
Background/Objectives: Androgen deprivation therapy (ADT) is commonly used for treatment of prostate cancer but is associated with side effects, such as sarcopenia and insulin resistance. The role of lifestyle factors such as diet and exercise on insulin sensitivity and body composition in testosterone-deficient males is poorly understood. The aim of the present study was to examine the relationships between androgen status, diet and insulin sensitivity. Subjects/Methods: Middle-aged (11–12 years old) intact and orchidectomized male rhesus macaques were maintained for 2 months on a standard chow diet and then exposed for 6 months to a Western-style, high-fat/calorie-dense diet (WSD) followed by 4 months of caloric restriction (CR). Body composition, insulin sensitivity, physical activity, serum cytokine levels and adipose biopsies were evaluated before and after each dietary intervention. Results: Both intact and orchidectomized animals gained similar proportions of body fat, developed visceral and subcutaneous adipocyte hypertrophy and became insulin resistant in response to the WSD. CR reduced body fat in both groups but reversed insulin resistance only in intact animals. Orchidectomized animals displayed progressive sarcopenia, which persisted after the switch to CR. Androgen deficiency was associated with increased levels of interleukin-6 and macrophage-derived chemokine (C-C motif chemokine ligand 22), both of which were elevated during CR. Physical activity levels showed a negative correlation with body fat and insulin sensitivity. Conclusions: Androgen deficiency exacerbated the negative metabolic side effects of the WSD such that CR alone was not sufficient to improve altered insulin sensitivity, suggesting that ADT patients will require additional interventions to reverse insulin resistance and sarcopenia.